A Study on the Restructuring of Social Work Course Content for People with Disabilities under the Background of the Establishment of Social Work Departments in Party Committees - Yue, Lijun; Chen, Shihai (Journal of Educational Research and Policies, 2025)
With the establishment of new Party Committee Social Work Departments, China’s governance system and service paradigm for disability services are undergoing systemic transformation. This study, based on an in-depth analysis of the functional positioning of Party Committee Social Work Departments, systematically explores their profound impact on disability social work in terms of goal orientation, service venues, and working models. An examination of the current curriculum reveals core problems such as weak political and policy content, a lack of collaborative governance perspectives, and a scarcity of local practical cases. Based on ecosystem theory and collaborative governance theory, this study proposes the core principle of unifying political and professional aspects and integrating theory and practice. It constructs a new “four-in-one” curriculum system encompassing value theory and policy literacy, professional knowledge and core skills, government-society collaboration and resource integration, and local practice and innovative applications. Furthermore, it proposes specific implementation paths from aspects such as innovative teaching methods, construction of practice bases, and optimization of the teaching staff, providing a systematic solution for promoting the transformation of disability social work education from a “professional-centric” to a “governance-centric” approach.